(untitled) (Eurasian Journal of Media and Communications, 2023)
Despite all the roles that language plays in human life, when various government agencies discuss health issues and challenges, they rarely mention language. as one of the factors that will contribute to the availability of good safety, care and treatment of diseases in a clear and simple way. In the place where the language was named, it was found that the law that will be used to protect it so that it takes root and bears good fruit is not hidden. This is the reason why this research looks at the value of language in obtaining good care and treatment of diseases, especially in the case of viruses and infectious diseases. Therefore, one of the research problems that we are looking for is the role of language in the protection, care and treatment of this disease which is a virus and a disease known in English as HIV/AIDS. The research findings of this article are based on personal research, interviews with various medical institutions and those obtained through internet channels. The findings of this research show that the protection, care and treatment of viruses and diseases will be easier and easier if language is seen as an indispensable tool in the protection, care and treatment of diseases. This is because it is through language that special and clear explanations will go from the teachers and health monitors to the patients. In the same way, patients will be able to explain themselves clearly to the teachers and health care providers. The researchers suggest that the federal government can put the language at a higher level whenever it is discussed about the protection and treatment of different diseases by making the students of health can have an education in ’matters of linguistic science (Linguistics) and included as one of their prophecies (Syllalus). Also, a multilingual typist is established between the patient and the doctor to ensure full understanding between the two, especially where both do not speak the same language to facilitate understanding There is a perfect balance between the two. This will ensure good protection and the treatment of the disease will be effective and permanent